2020
DOI: 10.1002/aoc.5919
|View full text |Cite
|
Sign up to set email alerts
|

Copper and nickel immobilized on cytosine@MCM‐41: as highly efficient, reusable and organic–inorganic hybrid nanocatalysts for the homoselective synthesis of tetrazoles and pyranopyrazoles

Abstract: In this work, a green approach is reported for efficient synthesis of biologically active tetrazole and pyranopyrazole derivatives in the presence of Cu-Cytosine@MCM-41 and Ni-Cytosine@MCM-41 (copper (II) and nickel (II) catalyst on the modified MCM-41 using cytosine). The synthesis of tetrazoles and pyranopyrazoles in the presence of these catalysts was performed in green solvents such as water or poly (ethylene glycol) (PEG). All products were obtained in high TOF (turnover frequency) numbers in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 90 publications
0
44
0
Order By: Relevance
“…Apart from using a trace amount of catalyst, nanocatalysis processes dramatically enhance the contact between the active component of the catalyst and reactants and therefore increase the rate and yield of chemical reactions 10 , 11 . A vast majority of the heterogeneous and homogenous catalysts are pertinent to transition metal nanoparticles due to their unprecedented physicochemical properties 12 15 . Among these tremendous efforts, nickel oxide nanoparticles have been developed as an efficient catalyst in the chemical synthesis of a wide range of valuable organic compounds such as spiro and condensed indole derivatives 16 , aromatic heterocycle 17 , 5-substituted 1 h-tetrazoles 18 , quinolines 19 , spirooxindoles 20 , polyhydroquinolines, and sulfoxidation 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from using a trace amount of catalyst, nanocatalysis processes dramatically enhance the contact between the active component of the catalyst and reactants and therefore increase the rate and yield of chemical reactions 10 , 11 . A vast majority of the heterogeneous and homogenous catalysts are pertinent to transition metal nanoparticles due to their unprecedented physicochemical properties 12 15 . Among these tremendous efforts, nickel oxide nanoparticles have been developed as an efficient catalyst in the chemical synthesis of a wide range of valuable organic compounds such as spiro and condensed indole derivatives 16 , aromatic heterocycle 17 , 5-substituted 1 h-tetrazoles 18 , quinolines 19 , spirooxindoles 20 , polyhydroquinolines, and sulfoxidation 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent Reactions (MCRs) are propitious condensation reactions 26 , 27 , in which integrate moieties of several starting materials to produce a desirable product 28 , 29 . This efficient chemical synthesis toolbox is of great interest due to high selectivity, bond-construction efficiency, and sustainability in providing complex molecules with promoted diversity 12 , 15 , 30 . Moreover, MCR are considered as a combinatorial synthesis approach in which a chemical reaction of all materials is occurred in one pot in a single step fashion producing a wide variety of organic compounds with relatively strict avoidance of waste formation 31 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The 2% of weight loss was attributed to the silanol condensation. [ 22,29–34 ] In the TGA analysis of 6–9 , the first weight loss was observed below 200°C because of the solvents and water on the surface and within the pores of 6–9. [ 67–69 ] It is very obvious from TGA curves that the weight loss of 6–9 in the first region show a decreased value compared with the first region of bare mesoporous materials with 6–9 , indicating that 6–9 have higher hydrophobic character than bare mesoporous materials.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16–19 ] SBA‐ and MCM‐type silicas are two of the most popular support materials used in the fixation of chiral catalyst via covalent bond due to their ordered structure, very high surface areas, uniform, tunable pore size, chemical composition, shapes, and surface properties. [ 20–26 ] Silyl derivatives of active catalysts can be grafted to the walls of silica supports by condensation of organosilane derivative of catalysts with Si‐OH groups on the surface of support materials. Prepared heterogeneous materials for the enantioselective catalysis have the advantages of the simplicity of removal, regeneration, and reusability of them.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction condition was optimized by varying catalyst loading, solvents, sodium azide Scheme 16 Synthesis of the Ni-cytosine@MCM-41 and Cu-cytosine@MCM-41 nano-catalyst. 123 concentration and temperature in the [3+2] cycloaddition of benzonitrile and sodium azide. It was observed that optimum results were obtained with 3.1 mol% Cu-cytosine@MCM-41 and 0.1 mol% of Ni-cytosine@MCM-41 catalyst loading in PEG-400 at 120 C using 1.3 mmol of sodium azide.…”
Section: Composite Nanomaterials Catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%